Factor Analysis on Culinary Business Owner Adoption of Green Practice - Nicholas Finn Silverio; Widjojo Suprapto; Wilma Laura Sahetapy (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2025)
Indonesia's culinary industry has experienced rapid growth, driven by the increasing number of young entrepreneurs and the advancement of digital platforms. However, this growth has been accompanied by significant environmental impacts, particularly from food packaging waste and leftover ingredients. On the other hand, consumer awareness of environmental issues has also increased, creating pressure on business owners to adopt environmentally friendly practices (green practices). Although green concepts such as biodegradable packaging and waste management are becoming more familiar, their adoption among culinary business owners remains limited. This situation has prompted research to understand the psychological and social factors influencing business owners' intentions to adopt green practices, using the Theory of Planned Behavior (TPB) as the analytical framework. This quantitative study involved 78 culinary business owners as respondents, with data collected via questionnaires and analyzed using Confirmatory Factor Analysis (CFA) in SPSS. The results identified four dominant factors influencing adoption intentions: social pressure and regulations, reputation motivation and technical confidence, perceptions of economic and environmental benefits, and strategic considerations for implementation.